The Role of The Korean Leadership of Dimsum Sidoarjo in Improving Employee Morale and Performance - Ega Rosita Dewi; Cucu Hayati (INCOME: Innovation of Economics and Management, 2023)
This study aims to analyze the role of Korean Dimsum Sidoarjo's leadership in improving employee morale and performance. Established on December 28, 2020, at Jl. Ponti no.9 Sidoarjo, East Java, Korean Dimsum Sidoarjo operates in the culinary field, offering a variety of Korean dimsum. Effective leadership guides motivates and organizes employees to achieve optimal performance. However, the leadership at Korean Dimsum Sidoarjo often needs more engagement with employees, is indecisive, and lacks a clear vision, resulting in low employee morale and performance. This study employs descriptive-qualitative research methods, using interviews and observation for data collection. The findings indicate that the leadership at Korean Dimsum Sidoarjo has made several efforts to improve employee morale and performance, such as providing training and motivation in the form of incentives and praise, but there are still challenges to overcome. These challenges include negative perceptions from employees when motivation is not given intensively, and the leadership needs to be more responsive in addressing employee issues.